Study of Gryllacridinae (Orthoptera: Stenopelmatidae) from Thailand and adjacent countries: the genera Ultragryllacris gen. nov. and Capnogryllacris - Gorochov, Andrej V.; Dawwrueng, Pattarawich; Artchawakom, Taksin (Zootaxa, 2015)
A new material on the genera Ultragryllacris gen. nov. and Capnogryllacris Karny, 1937 from Thailand, Laos and Cambodia is considered. Five new species and subspecies are described: U. pulchra sp. nov.; U. p. alboclypeata subsp. nov.; C. thaica sp. nov.; C. sakaerat sp. nov.; C. phaeocephala cambodiensis subsp. nov. Capnogryllacris s. l. is divided into two possible subgenera (Capnogryllacris s. str. and Dictyogryllacris Karny, 1937, stat. nov.) as a minimum; the former genera Borneogryllacris Karny, 1937, syn. nov., Marthogryllacris Karny, 1937, syn. nov. and Erythrogryllacris Karny, 1937, syn. nov. are treated as synonyms of the subgenus Capnogryllacris. Previously unknown female for C. khmerica Gorochov, 2003 is described; neotype for C. martha (Griffini, 1914 ), type species of Marthogryllacris, is designated; C. erythrocephala Gorochov, 2003, sp. ressur. and C. e. borealis Gorochov, 2003, stat. ressur. are restored from synonyms of C. martha and from species status, respectively.